Intersectionality and Climate Justice: A Literature Review on Gender, Equity, and Sustainable Development (Prakriti - The International Multidisciplinary Research Journal, 2025)
The impacts of climate change are unequally distributed around the globe, especially in developing countries. Studies have shown that the effects of climate change are not gender-neutral. Due to the debate over climate change, the movement for climate justice has expanded since its inception, including concerns of ethics, equality, gender, racism, and human rights. The effects of climate change are evident in all segments of the global population who depend on natural resources for their livelihood or are least equipped to handle natural calamities. Gender inequality integrated with the climate crisis is regarded as one of the significant challenges of our time. When gender issues are mentioned in any discussions related to climate change it is usually concerning women’s gendered vulnerability in current society especially in rural areas of the developing countries. This not only poses threats to livelihood and health but also to the safety and security of girls and women in developing countries across the globe. Women in society commonly face greater risks and burdens from the immediate impacts of climate change in situations related to poverty. Climate change also intensifies other societal problems among girls and women such as gender-based violence. Women, elderly people and children spend most of their time indoors leaving them at greater risk for vulnerability during disasters. Furthermore, it is evident that women's uneven involvement in decision-making processes exacerbates existing disparities by limiting their ability to fully participate in planning, policy-making, and implementation linked to climate change. However, because of their local understanding of sustainable resource management and practices at the family and community levels, women may play a critical role in adapting to the effects of climate change. Diversity, equity and inclusion should be the key drivers in achieving gender justice to fulfil the motto of SDGs of leaving no-one behind. The paper will try to analyse how gender justice and inclusivity play a role in achieving the goals leading towards climate justice and can help in the creation of liveable and resilient cities.
Keywords: climate justice; gender-inclusivity; diversity; inclusive; climate change